Electrochemical Sensing and High Selective Detection of Hesperidin with Molecularly Imprinted Polymer Based on Ultrafine Activated Carbon. Issue 15 (1st January 2019) - Sun, Bolu; Hou, Xiaohui; Li, Dai; Gou, Yuqiang; Hu, Fangdi; Li, Wen; Shi, Xiaofeng
Abstract : As hesperidin is a key indicator of some herbs and traditional Chinese medicine preparations, it is important to realize its sensitive, fast and high selective detection. In this work, prepared ultrafine activated carbon with high electrical conductivity was introduced as base decorated material of electrode, then with the use of self-assembly method and electro-polymerization method, the molecularly imprinted polymer was prepared on the electrode by using hesperidin as template molecular and o-aminothiophenol as functional monomer. Scanning electron microscope, cyclic voltammetry and electrochemical impedance spectroscopy were employed to characterize the morphological features and the stepwise modification of electrode, separately. The influence of pH, ratio of monomer to template, self-assembly time and so on were investigated and optimized. Under the optimized condition, the fabricated sensor exhibits a wide linear range from 85nM to 30μM with a low detection limit of 45nM. The decorated sensor has favorable selectivity, reproducibility and stability that could be used in real sample analysis.